Absolute yields of the exciton induced desorption at the surface of solid rare gases - Arakawa, I.; Adachi, T.; Hirayama, T.; Sakurai, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Absolute yields of the photo-induced desorption at the surface of solid rare gases were studied in the excitonic excitation region. Both metastable and total desorption yields depend strongly on excitation energy and film thickness of rare gas solids. The absolute desorption yields and their dependenceon film thickness were quantitatively reproduced by a simulation based on the diffusion of excitons in the bulk and the kinetic energy release by a cavity ejection mechanism and an excimer dissociation one followed by internal sputtering.